Building Resilience Against Bullying in Indonesian Boarding Schools: Relational and Institutional Mechanisms of Recovery - Sumarni, Sri (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
Bullying among adolescents does not always appear as overt physical aggression. In boarding school settings, it often operates through teasing, labeling, gossip, and subtle forms of exclusion that are frequently normalized as ordinary peer interaction. This article examines how resilience against bullying is formed in two Indonesian boarding schools, SMP Bumi Cendikia Yogyakarta and SMP Muhammadiyah Padang Panjang Boarding School. Using a qualitative case study design, the study draws on observations, interviews, and documentation collected over a 7-month period. The findings show that bullying in these settings is predominantly social-verbal and often emerges through joking practices, repeated nicknames, and gossip that gradually produce shame, withdrawal, and social insecurity. The study also finds that resilience is not primarily an individual trait. Rather, it is built through layered support involving family guidance, emotional accompaniment by dorm supervisors and counseling staff, formal reporting channels, and active facilitation of victims’ re-entry into peer relations. The article argues that resilience in boarding schools is relationally and institutionally scaffolded. Recovery depends not only on stopping harmful behavior but also on restoring students’ sense of belonging, safety, and everyday participation in school life.